Exploring Psychological Constructs as Predictors of Life Satisfaction Among Adolescents with Absentee Parents - Sealmoy, Lendi Lee A.; Marañon, Noel S. (Philippine Social Science Journal, 2020)
Most schools aim to produce holistically developed individuals; however, initiatives fostering life satisfaction and well-being are not substantial or even neglected. Likewise, globally, adolescents are confronted with various situations influencing how they view and evaluate their lives. One of these factors is parental absence. Consequently, this paper describes the degree of grit, the extent of resilience and self-control, and the level of life satisfaction of adolescents with absentee parents. Likewise, it establishes correlations among the three psychological constructs grit, resilience and self-control, and life satisfaction. Furthermore, it explores whether the three constructs predict life satisfaction.